2017
DOI: 10.1044/2017_aja-16-0116
|View full text |Cite
|
Sign up to set email alerts
|

High Risk Factors Associated With Early Childhood Hearing Loss: A 3-Year Review

Abstract: Certain risk factors place a child at significantly greater risk of congenital hearing impairment or developing permanent hearing loss by age 3. Follow-up diagnostic testing should remain a priority for children with certain risk factors for hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 36 publications
(38 reference statements)
1
30
1
7
Order By: Relevance
“…Categorical data including NICU care, ventilator dependence, oxygen requirement of any kind, aminoglycoside exposure, and family history demonstrated statistical significance for hearing loss compared to the control cohort. While other studies have demonstrated associated risks between hearing loss and younger gestational age and birth weights, our study variables showed only small effect size between groups (Beswick et al, 2012;van Dommelen et al, 2015;Dumanch et al, 2017). This may be due to patient stratification schemes in prior studies using birth weight (low, very low, etc.)…”
Section: Discussioncontrasting
confidence: 75%
“…Categorical data including NICU care, ventilator dependence, oxygen requirement of any kind, aminoglycoside exposure, and family history demonstrated statistical significance for hearing loss compared to the control cohort. While other studies have demonstrated associated risks between hearing loss and younger gestational age and birth weights, our study variables showed only small effect size between groups (Beswick et al, 2012;van Dommelen et al, 2015;Dumanch et al, 2017). This may be due to patient stratification schemes in prior studies using birth weight (low, very low, etc.)…”
Section: Discussioncontrasting
confidence: 75%
“…Although there is good evidence that some risk factors are associated with hearing loss (Dumanch et al, 2017), investigators have questioned the utility of other risk factors included in screening or surveillance programs because of the low yield of late-onset PCHL (Wood et al, 2013) and changes in standards of care (Beswick et al, 2012;Beswick et al, 2013;Lü et al, 2011;O'Connor et al, 2013). Surveillance programs are costly for both the health system and parents (The Joint Committee on Infant Hearing, 2019); therefore, updating knowledge on risk factors for PCHL is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Syndromes associated with hearing loss and craniofacial anomalies are strongly predictive of postnatal hearing loss, with craniofacial anomalies inversely related to the risk of progressive hearing loss. 15,16 The prevalence of JCIH risk factors in children with UHL or BHL has been studied independently. 12,17 To our knowledge, no studies have compared JCIH risk factors among groups of children with UHL or BHL.…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Syndromes associated with hearing loss and craniofacial anomalies are strongly predictive of postnatal hearing loss, with craniofacial anomalies inversely related to the risk of progressive hearing loss. 15,16…”
Section: Introductionmentioning
confidence: 99%